Business Strategy To Win The Competition Among Property Industry (The Indonesian Journal of Business Administration, 2014)
Abstract –  PT Gagas Gemilang has issued a new cluster-type housing with the name "Panam View Residence". Concept promoted by the type of housing that is modern-ethnic, where elements of a modern minimalist concept combined with a little ethnic touch to the building that is offered is not monoton. Research was carried out on a property company who have difficulty in marketing their products. As for in terms of location, the location of housing included in the development of the city. The technique used in this method is to collect data and information to be analyzed in order to generate predictions as a preparation for decision making process. This method give an overview of early warning, implications and options in each scenario drawn from the analysis of external and internal as recommendation for the company which could be used as a reference in determining and developing company’s business strategy.  Keywords: Panam View Residence, PT Gagas  Gemilang, Marketing Strategic, Property sector, Housing Development.